Modern terrorism as a social phenomenon: nature and forms - Мокляк, Володимир Вікторович (Problems of legality, 2016)
The article reveals the essence of terrorism as a phenomenon of social reality through the prism of the theory. The reasons of different understanding of this phenomenon are analysed. The article provides differentiation between primary and intermediate targets of terrorist activities. Thus, the main (general, strategic, ultimate) goal of terrorism is to achieve certain political, religious or other social changes, and intermediate (tactical, local) terrorism objectives and define the specific manifestations of it. It is noted that terrorist activity always involves the use of extreme violence or the threat of its use. Manifestations of the abovementioned violence are varied and are independent acts, the commission of which entails criminal liability. The peculiarity of violence caused by terrorism is the use of «victim-target differentiation» strategy. Thus, terrorism aim at creating atmosphere of fear, terror, tension and intimidating the population, or some part of it. This state is generated 1) by the terrorist acts (the brutal violence and its consequences, the greater the psychological affect it can have on third parties); 2) random and indiscriminate nature of the selection of victims; 3) unexpected and unpredictable violence. Other features of modern terrorism are determined: mainly organized nature; close ties with organized crime; armament and conspiration; widespread use of the media and others. The article gives grounds to interpret terrorism as a separate kind of crime. It is determined that criminal forms of terrorism are covered as separate components of terrorist offenses (Art. 258-258-5 of the Criminal Code of Ukraine), and other elements of crimes, which also comply characteristics of terrorist offenses (attempt on the life of the state or public figure, hostage-taking, threat to commit theft or use of radioactive materials, attempt on the life of a foreign state representative, etc.).